2013
DOI: 10.9790/0837-0711316
|View full text |Cite
|
Sign up to set email alerts
|

“Effect of Reinforcement on Teaching – Learning Process”

Abstract: The concept of reinforcement is identical to the presentation of a reward. The present study deals with the importance of reinforcement in teaching-learning process. The data has been collected from five schools in Bongaon Municipal Area, North 24 Pgs, West Bengal, India. A total of hundred (100) students of class-IX were taken who had been equally divided into experimental groups and control groups. The main independent variable for the present study was reinforcement. The dependent variable in the study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 3 publications
4
9
0
Order By: Relevance
“…This is in line with the result of study conducted by Pratiwi (2015) which showed that more than half of students agreed it helped them improving students' grade. This is also supported by the study by Hoque (2013) which showed that students treated by positive reinforcement was performing better.…”
Section: Students' Perceptionsupporting
confidence: 60%
“…This is in line with the result of study conducted by Pratiwi (2015) which showed that more than half of students agreed it helped them improving students' grade. This is also supported by the study by Hoque (2013) which showed that students treated by positive reinforcement was performing better.…”
Section: Students' Perceptionsupporting
confidence: 60%
“…Therefore, positive reinforcement is essential to be applied by teachers during school from home. Hoque (2013) states that one of the essential elements in the teaching process is providing reinforcement to students. Therefore, the skill of giving reinforcement must be mastered by the teachers because the reinforcement given to students can increase student motivation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on observation, the researcher found that the English teacher used both positive and negative reinforcement. Although the teacher use both of them, but researcher can observ, the english teacher use positive reinforcement dominantly for the first grade students of SDIT Padang Islamic School.According to (Hoque, 2013), giving positive reinforcement to the students gave positive contribution to the students' affective, cognitive and psychomotor aspects. In line with that, this study was focused only on positive reinforcement because through positive reinforcement, it would stimulate the students to redo their positive behavior.…”
Section: Resultsmentioning
confidence: 99%